In the Hurricane's Eye : The Troubled Prospects of Multinational Enterprises. - Vernon, Raymond (Cambridge : Harvard University Press, 1998)
The world's multinational enterprises face a spell of rough weather, Vernon argues, not only from the host countries in which they have established their subsidiaries, but also from their home countries. The challenge for policy makers, Vernon argues, is to bridge the quite different regimes of the multinational enterprise and the nation-state.
Intro -- Contents -- Preface -- 1. SETTING THE CONTEXT: Multinational Enterprises in a System of Nation-States -- A Rough Take-off for the Multinationals -- Calibrating the Multinationals' Importance -- Multinationals' Behavior in International Markets -- The Challenge: Accommodating Multinationals and Nation-States -- 2. TENSIONS IN THE BACKGROUND: Conflict between Multinational Enterprises and Nation-States -- The Nation-States' Struggle for Jobs -- Taxing Multinationals -- Security for the Nation-State -- Conflicts of Jurisdiction, Culture, and Principle -- 3. INSIDE THE EMERGING ECONOMIES: High Stakes for Nation-States and Multinational Enterprises -- Latin America -- Fading Stars of Asia -- Transitional Economies: From Hungary to China -- India -- Conclusions -- 4. INSIDE THE INDUSTRIALIZED ECONOMIES: New Sources of Tension -- The Case of Europe -- The Case of the United States -- The Case of Japan -- Common Problems, Common Responses -- 5. THE STRUGGLE OVER OPEN MARKETS: The Gathering Clouds -- Ambivalence in the United States and Europe -- Multinationals and the Struggle for Public Resources -- Uncertainties in the International Political Climate -- 6. RIGHTING THE BALANCE: Possible Policy Responses -- The Search for Global Principles -- Bilateral Agreements -- Industry-Centered Agreements -- Regional Agreements -- Possible New Initiatives -- Unilateral Measures -- Reprise -- Notes -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: International business enterprises; Host countries (Business)-Economic policy; Competition, International; Pressure groups; Electronic books